The Influence of Child Caregivers' Personal Hygiene and Family Smoking Behavior on Stunting - Zahtamal; Rosadi, Tia Masita; Restila, Ridha; Sundari (Universitas Airlangga, 2024)
Background: Stunting is a problem that still occurs in Indonesia. It is a chronic nutritional problem associated with insufficient food intake so that nutritional needs are not fulfilled over a long period. Stunting also can be caused by indirect factors such as environmental and behavioral. Aims: This study aimed to analyze the correlation of child caregivers' personal hygiene implementation and family smoking behavior on the occurrence of stunting. Methods: This type of research is an analytic survey with a case-control study approach. The number of respondents was 25 cases and 25 controls so the total number of respondents was 50 respondents. Results: The results of the examination found that personal hygiene of caregivers and smoking habits in the families of stunted toddlers were mostly inadequate and there was a smoking habit in the families of stunted toddlers. There is a significant relationship between defecation behaviors and the incidence of stunting with a p-value of 0.02 (<0.05). Based on multivariate analysis, it was found that unqualified defecation behaviors had a 63.3% probability of stunting. Conclusion: There is a significant correlation between defecation behaviors and the occurrence of stunting with a p-value of 0.02 (<0.05). According to multivariate analysis, respondents with defecation behaviors that did not meet the standards had a 4.03 times greater risk of having a child with stunting.